2012
DOI: 10.1097/scs.0b013e31824e6ca7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Limitations of Posterior Tympanotomy

Abstract: To radiologically evaluate the anatomic factors that may determine the view field or the accessibility of the posterior tympanotomy into the posterior mesotympanum, a cohort of 30 patients with pneumatic mastoids and 30 patients with unilateral sclerotic mastoids were included. Anatomic relationships were evaluated according to 5 parameters. The reference parameter of the view field through posterior tympanotomy was the maximum view to the stapes area through posterior tympanotomy. Direct distance between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…In this study, there was one case with an overhanging posterior wall, and one with a high riding jugular bulb. In our cohort and in previous studies, the obscuration of the facial recess opening by the posterior wall or sigmoid sinus and jugular bulb is a rare phenomenon (< 1%) [14,18]. Some surgeons advocate in cases of an overhanging posterior wall, to "green stick fracture" the posterior wall medially (just lateral from the FN and push it forward) providing improved exposition of the RWM, access to the middle ear and perform implantation of the electrode array; then replace the (partly mobile) canal wall to its previous position where bone will regrow.…”
Section: Operative Reportsupporting
confidence: 67%
See 1 more Smart Citation
“…In this study, there was one case with an overhanging posterior wall, and one with a high riding jugular bulb. In our cohort and in previous studies, the obscuration of the facial recess opening by the posterior wall or sigmoid sinus and jugular bulb is a rare phenomenon (< 1%) [14,18]. Some surgeons advocate in cases of an overhanging posterior wall, to "green stick fracture" the posterior wall medially (just lateral from the FN and push it forward) providing improved exposition of the RWM, access to the middle ear and perform implantation of the electrode array; then replace the (partly mobile) canal wall to its previous position where bone will regrow.…”
Section: Operative Reportsupporting
confidence: 67%
“…These results show that the FN-CTN distance indeed provides a realistic estimate of the size of the 'window' to the middle ear structures [16]. A previous study also showed that the FN-CTN distance in the mastoid is important for the viewing angle through the facial recess opening [18]. Two other studies in adults showed no effect of the facial recess width on the visibility of the RW [10,12].…”
Section: Facial-chorda Tympani Nerve Distancesupporting
confidence: 57%
“…Several studies have sought to establish radiologic measurements that can predict degree of visualization during a standard facial recess approach (42,68,69). Of particular interest are the total FR area, the EAC angle and FN location.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Lee et al reported that the angle between the cortex of the external ear canal and the FN was highly correlated with visibility through posterior tympanotomy. 42 They suggested that pneumatic mastoids, but not sclerotic mastoids, could have a more complex relationship with FR anatomy, including various other factors that were not considered in their study.…”
Section: Discussionmentioning
confidence: 93%